Translators in the Loop: Observing and Analyzing the Translator Experience with Multimodal Interfaces for Interactive Translation Dictation Environment Design - Zapata Rojas, Julian (Université d'Ottawa / University of Ottawa, 2016)
This thesis explores interactive translation dictation (ITD), a translation technique that involves interaction with multimodal interfaces equipped with voice recognition (VR) technology throughout the entire translation process. Its main objective is to provide a solid theoretical background and an analysis of empirical qualitative and quantitative data that demonstrate ITD’s advantages and challenges, with a view to integrating this technique into the translation profession. Many empirical studies in human-computer interaction have strived to demonstrate the efficiency of voice input versus keyboard input. Although it was implicit in the earliest works that voice input was expected to completely replace—rather than complement—text-input devices, it was soon proposed that VR often performed better in combination with other input modes. This study introduces multimodal interaction to translation, taking advantage of the unparallelled robustness of commercially available voice-and-touch-enabled multimodal interfaces such as touch-screen computers and tablets. To that end, an experiment was carried out with 14 professional English-to-French translators, who performed a translation task either with the physical prototype of an ITD environment, or with a traditional keyboard-and-mouse environment. The hypothesis was that the prototypical environment would consistently provide translators with a better translator experience (TX) than the traditional environment, considering the translation process as a whole. The notion of TX as introduced in this work is defined as a translator’s perceptions of and responses to the use or anticipated use of a product, system or service. Both quantitative and qualitative data were collected using different methods, such as video and screen recording, input logging and semi-structured interviews. The combined analysis of objective and subjective usability measures suggests a better TX with the experimental environment versus the keyboard-and-mouse workstation, but significant challenges still need to be overcome for ITD to be fully integrated into the profession. Thus, this doctoral study provides a basis for better-grounded research in translator-computer interaction and translator-information interaction and, more specifically, for the design and development of an ITD environment, which is expected to support professional translators’ cognitive functions, performance and well-being. Lastly, this research aims to demonstrate that translation studies research, and translation technology in particular, needs to be more considerate of the translator, the TX, and the changing realities of the interaction between humans, computers and information in the twenty-first century.
Keywords: translation technology; multimodal interaction; human-computer interaction; human-information interaction; user experience; voice recognition